(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2024)
The article explores the Luigi Meneghello’s unpublished translations into Vicentine dialect of selected texts by John Donne. Through the examination of avant-textual materials and the genetic reconstruction of the texts, the study conducts an analysis of selected passages that exemplify the methods by which the author adapts the original poems to the Vicentine cultural and linguistic system. The translations are then situated within the broader context of Meneghello’s literary work. In the appendix is provided the translation of The Good-Morrow.